Dos nuevos taxa del género grallaria (aves: formicariidae) del alto valle del magdalena (colombia) (1979)
Two new subspecies belonging to very scarcely known species of antpittas are named: G. rufocinera romeroana (type locality: near the Bedón River waterfalls, Puracé Natural National Park, Dept. of Huila, ca. 3.000 m.) recognizable by its solid rufous gular region and developed white "scaled" pattern in the belly, and G. alleni andaquiensis (type locality: vicinity of the Guácharos Cave, Cueva de los Guácharos, Natural National Park, Dept. of Huila, ca. 2.000 - 2.100 m.) recognizable by smaller (wing) size, and darker upper parts, throat and belly.